Impact of Multimorbidity Subgroups on the Health Care Use and Clinical Outcomes of Patients With Tuberculosis: A Population-Based Cohort Analysis - Chen, Qin; Che, Yang; Xiao, Yue; Jiang, Feng; Chen, Yanfei; Zhou, Jifang; Yang, Tianchi (Frontiers in Public Health, 2021)
Background: Multimorbidity is defined as the existence of two or more chronic health conditions in the same individual. While patients with tuberculosis commonly had multiple conditions at diagnosis, such as HIV, diabetes and depression, to the authors’ knowledge, there is limited information on the patterns of multimorbidity, and how the types and combinations of conditions could impact the healthcare utilization, expenditures, and TB outcomes. Methods: An observational cohort study of adult patients diagnosed with tuberculosis was conducted using the Chinese Center for Disease Control and Prevention (CDC) TB registry linked to Ningbo Regional Health Care Database (NRHCD) (2015-2020). Latent class analysis was used to identify comorbidity groups among the subset with ≥2 conditions including TB. Group-level health care use, expenditures and treatment outcomes were compared with patients without chronic conditions using multivariate regression models. Results: A total of 9,651 patients with TB were identified, of whom approximately 61.4% had no chronic conditions, 17.4% had 1 chronic condition, and 21.3% had ≥2 chronic conditions. Among those with ≥1 chronic condition other than TB, 4 groups emerged: 1) general morbidity (54.4%); 2) cardiovascular morbidity without complications (34.7%); 3) cardiovascular morbidity with complications (5.0%); 4) respiratory morbidity (5.9%). The respiratory morbidity group experienced the highest expenditures, at 16,360 CNY more overall (95% CI, CNY 12,615-21,215) after adjustment compared with TB patients without chronic conditions. The respiratory morbidity and cardiovascular morbidity with complications group also had the lowestest odds of favorable TB outcomes (adjusted odds ratio (aOR), 0.68; 95% CI, 0.49-0.93) and (aOR 0.59, 95%CI 0.42-0.83), respectively. The cardiovascular morbidity without complications group had the highest odds of successful TB treatment (aOR, 1.40; 95% CI, 1.15-1.71). Conclusions: Multimorbidity is common among patients with TB. The current study identified four distinct comorbidity subgroups, all of which experienced high, yet differential, rates of health care use. These findings highlight the needs for urgent reforms to transform current fragmented TB care delivery and improve access to other specialists and financial assistance.